2005
DOI: 10.1111/j.1462-5822.2005.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple virulence factors are required for Staphylococcus aureus-induced apoptosis in endothelial cells

Abstract: SummaryStaphylococcus aureus infections can result in sepsis and septic shock associated with vascular damage and multiple organ failure. Apoptosis appears to play a key role during sepsis, and the ability of S. aureus to induce apoptosis in endothelial cells might contribute to metastatic infection. In contrast to leukocytes, in human umbilical vein endothelial cells and two endothelial cell lines neither purified a a a a -toxin nor staphylococcal supernatants were sufficient to induce apoptosis. Apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 57 publications
13
135
1
1
Order By: Relevance
“…This proteolytic activity in the vicinity of the vegetation has 2 consequences: one is to promote lysis of the vegetation itself and dissemination of septic emboli, and another is to promote degradation of the extracellular matrix and invasion of the underlying tissue, leading to valvular damage and/or abscess formation. 47,48 In conclusion, our present study demonstrated that 99m…”
Section: Rouzet Et Alsupporting
confidence: 52%
“…This proteolytic activity in the vicinity of the vegetation has 2 consequences: one is to promote lysis of the vegetation itself and dissemination of septic emboli, and another is to promote degradation of the extracellular matrix and invasion of the underlying tissue, leading to valvular damage and/or abscess formation. 47,48 In conclusion, our present study demonstrated that 99m…”
Section: Rouzet Et Alsupporting
confidence: 52%
“…However, rsp mutation neither influences internalization of S. aureus by HeLa cells nor phagosomal escape (SI Appendix, Fig. S2), both of which have been shown to be associated with cytotoxicity (29)(30)(31). Thus, our data suggest that rsp-defective S. aureus remain within the host cell longer and delay pathogen-induced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome is usually determined by virulence factors and host response (15,16,18,21,24,36). Many virulence factors have been implicated in invasiveness, disease severity, and persistent bacteremia (1,8,10,11,12,24,30,36). Several studies have shown that methicillin-resistant S. aureus (MRSA) isolates are associated with higher mortality (5,32,33,36).…”
mentioning
confidence: 99%